Exploring Ethnomathematical Geometry in Indonesian Shadow Puppetry Gunungan: Philosophical and Educational Implications - Miftakhul Djannah; Naufal Ishartono; Argenti Agung Hayuni; Atikah Mufidah; Suliadi Fidaus bin Sufahani; Mohamad Waluyo (Universitas Muhammadiyah Surakarta, 2024)
This study delves into the philosophical dimensions of traditional architecture and the ethnomathematical geometry inherent in the mountains of shadow puppets, a significant aspect of Indonesia's cultural heritage. Utilizing a qualitative methodology with an ethnographic design, data were collected through observations and interviews with primary, secondary, and additional informants. The objective of this research is to uncover the mathematical concepts embedded in the mountains of shadow puppets, including geometry, algebra, arithmetic, and statistics, using an ethnographic approach that addresses four principal inquiries: